HOMOSEXUALITY: A SCIENTIFIC VIEW - Ahmed, Jaafar Omer; Qasab, Zana Ahmad; Saeed, Sarhang Ibrahim (Transpublika Publisher, 2024)
Homosexuality has a long history. The public is exposed to scientific findings through media reports; there are many misunderstandings about homosexuality; and as a result, a person who has homosexual feelings suffers minor stress. Two different directions have emerged. One believes that homosexuals are responsible for the spread of diseases. The second one believes that homosexuality is a normal behavior. The main goal of this narrative review is to revisit this issue, emphasizing the need for consistent interpretation and ongoing research. This review is framed using insights from recent scientific resources. Four main terms related to homosexuality (sex, gender, gender identity, and sexual orientation) and their dimensions are discussed. Some data about homosexual orientations and behaviors are explained. Homosexuality in the past and present, its history as a mental disorder until its removal from textbooks, and its relationship with mental health are mentioned. The reasons why a person is homosexual are multifaceted, etiologically complex, and unclear. Both views—biological and environmental factors—are clarified. Changes in the understanding of homosexuality continue due to the influence of politics, society, and religion. We need more research to better understand the phenomenon, all aspects of the causes, and how to deal with them. These efforts must be free from political and religious directions.